Urdiduras museais e tramas expositivas no Museu de Artes e Ofícios e no Museu do Escravo de Belo Vale - Wagner Lucas Pereira (2022)
The present research is outlined by the problematization around the contribution of material culture studies to the production of knowledge in the field of Museology. The research was conducted by the following question: To what extent can research results in the field of material culture positively impact expository narratives, from the perspective of knowledge construction? For this, two museums were chosen as objects of study: The Arts and Crafts Museum (Museu de Artes e Ofícios) located in Belo Horizonte - MG, Brazil and the Slave Museum (Museu do Escravo) located in Belo Vale - MG, Brazil. Thus, the research was divided into two moments. At first, incursions were carried out in an attempt to highlight the historical trajectory of the institutions, their respective creation processes and the agents involved. In the second moment, movements were carried out with the objective of promoting theoretical guidelines and methodological models for the analysis of museological exhibitions based on the notion of the nuclear role of the material object. The work made use of several theoretical discussions and methodological tools improved in the disciplinary field of Museology and conceived intersections with strands of studies in which potentialities to improve museological praxis can be seen.